Unraveling the Impact of Physical Activity Patterns on Psychological Stress in Nursing Students: Evidence from the COVID-19 Crisis - Wibisono, Suryo; Syahruramdhani, Syahruramdhani; Kittipayak, Samrit (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2025)
Background: During the COVID-19 outbreak, many citizens were asked to stay at home in self-quarantine, which can be difficult in terms of remaining physically active and maintaining mental health. Objective: The goal of this study was to examine the relationship between physical activity and stress levels among nursing students during the COVID-19 pandemic. Methods: The correlational method was used in this study. A cross-sectional method was used. The participants in this study were nursing students from the Faculty of Medicine and Health Sciences. The sampling method used was simple random sampling, and the sample size was 219 students. The IPAQ and PSS-10 questionnaires were used in this study as instruments and then analysed using Spearman Rank. Results: According to the Spearman test results, the value of sig. (2-tailed) is 0.274, which is p > 0.05. It showed a relationship with an insignificant correlation value in the cross-tabulation correlation test. Conclusions: Physical activity and stress levels among nursing students do not significantly correlate during the COVID-19 pandemic. These findings highlight the importance of physical activity in maintaining psychological well-being among nursing students in times of crisis.